Assessment of Automotive Coatings Used on Different Metallic Substrates. (29th April 2014) - Bensalah, W.; Loukil, N.; Wery, M. De-Petris; Ayedi, H. F.
Abstract : Four epoxy primers commonly used in the automotive industry were applied by gravity pneumatic spray gun over metallic substrates, specifically, steel, electrogalvanized steel, hot-dip galvanized steel, and aluminum. A two-component polyurethane resin was used as topcoat. To evaluate the performance of the different coating systems, the treated panels were submitted to mechanical testing using Persoz hardness, impact resistance, cupping, lattice method, and bending. Tribological properties of different coating systems were conducted using pin on disc machine. Immersion tests were carried out in 5% NaCl and immersion tests in 3% NaOH solutions. Results showed which of the coating systems is more suitable for each substrate in terms of mechanical, tribological, and anticorrosive performance.